The Role of Physical Activity in Managing Epilepsy in Children and Adolescents: A Systematic Review - Pysiewicz, Wiktoria; Garbarczyk, Wiktor; Napieralska, Agnieszka; Kapla, Albert; Černohorská, Alicja; Bednarczyk, Daria; Białeta, Julia; Siembab, Karolina; Rowińska, Katarzyna; Jurkiewicz, Michalina (Quality in Sport, 2025)
Epilepsy is one of the most predominant neurological disorders in children and adolescents. It is characterized by recurrent, unprovoked seizures. While pharmacological treatments remain the primary approach for seizure control, non-pharmacological interventions like physical activity (PA) appear as potential complementary strategies for improving health outcomes in pediatric population. This systematic review evaluates the role of physical activity in the management of epilepsy in children and adolescents, focusing on its impact on seizure control, cognitive function, psychological well-being, and overall quality of life. Although the evidence regarding the impact of PA on seizure frequency is limited, regular physical activity has been shown to improve cognitive outcomes, mental health, and general quality of life in children with epilepsy. Safety concerns regarding PA of children with epilepsy are discussed. Further research among the pediatric population is needed, since PA might play an important role alongside conventional therapies in managing epilepsy in children and adolescents.